Analisis Faktor-Faktor yang Mempengaruhi Keputusan Pembelian Ikan Hias Air Tawar di Wilayah Bogor - Abdillah, Rizal; Masithoh, Siti; Yoesdiarti, Arti (Universitas Djuanda, 2022)
This study aims to determine the characteristics of freshwater ornamental fish consumers, determine the decision-making process of freshwater ornamental fish consumers, and determine the correlation between consumer behavior and purchasing decisions of freshwater ornamental fish in Bogor. The research held from October to November 2021 at three ornamental fish stores in Bogor (Terang Aquarium, Laladon Ornamental Fish Exchange, Bogor Ornamental Fish Marketing Depot). 50 respondents chosen by accidental sampling technique. The results showed that the consumer characteristics of freshwater ornamental fish varied which were known from the factors of gender, age, education, profession, family of responsibility, monthly income, monthly expenses for freshwater ornamental fish and when they start to buy/keep freshwater ornamental fish. Consumer’s considerations in buying/maintaining freshwater ornamental fish are in terms of how to care, price, ornamental fish’s behavior, size, color, shape, type of ornamental fish and where to buy. The results of the Spearman Rank Correlation analysis show that the cultural variable (X1) has a weak but significant correlation with the purchase decision (Y). The social variable (X2) has a very weak and insignificant correlation. The personal variable (X3) has a weak but significant correlation and the psychological variable (X4) has a strong and significant correlation with a correlation coefficient value is 0.642 and significant value less than 0.05 (0.000 < 0.05). Keywords: freshwater ornamental fish, consumer behavior, purchasing decisions, correlations